TRANSITION FROM KINDEGARDEN TO SCHOOL - USM ADMIN (Moldova State University, 2013)
Transition to School is a crucial step that influences the child's behavior and personality. Many researches sees the transition as a process that includes many players: children, families, educators, community, professionals and the whole system. Transition is the time when everyone has to be involved and take responsibility. Keyword: challenge, anxiety, complexity.